(untitled) (GYMNASIUM, 2008)
The research paper displays a study conducted on children suffering from severe autism disorders and aims to enhance the sensory motor abilities, especially the proprioception deficits within this disease, using several elements of Bobath method. The current study was applied on subjects during a year and three months on a sample of three autistics suffering from severe autism. The paper triggers on the autistic’s child sensory disorders, particularly on proprioception disabilities, recording the fact that applying the kinesitherapy method could lead to a better corporal posture, an improved dynamic and static balance, keener coordination and controlled motility abilities and altogether to a better interaction with the child. It is notably remarked that the progress in the therapeutical activity was also achieved through the disciplinary team work.